Improvement of Development Efforts Adolescent Health Services Care In Puskesmas Kota Surabaya through the Promotion Mix - Sufiah Rahmawati (JURNAL PENELITIAN KESEHATAN, 2016)
Adolescent Health Services Care (AHSC) is a model of health care for adolescents in health centers. AHSC in Surabaya contained in 13 health centers. The number of visits during the teenage 2012-2013 shows the overall coverage AHSC increased but has not reached the desired target by 80%. The purpose is developing effort to increase the utilization of health care services in AHSC through the promotion mix in Surabaya. This research was conducted in June 2015 and December 2015 using a cross sectional study design. The research location in Puskesmas Kota Surabaya. The study population was Young who visited to Puskesmas Kota Surabaya with AHSC teenagers as many as 2,078 peoples. The sample is 10 teenagers at every Puskesmas that has AHSC the number of respondents as many as 130 peoples were obtained using the formula of simple random sampling. The instrument used questionnaire which the validity and reliability test. The Result on the utilization of AHSC Puskesmas Kota Surabaya shows that only 2 independent variables that significantly influence the utilization of AHSC Puskesmas Kota Surabaya in adverstising and Personal selling. Recommendation is increased creativity to develop media campaign by involving teens, Creation Care for AHSC material is made more attractive and curriculum renewal. Mix Promotion through personal selling and direct marketing as well, need to be facilitated by the MoU between the health center and school health centers strengthening the internal environment of the increase in awareness of the teenagers who come to Puskesmas for all workers in AHSC.  Keywords:  Promotion Mix, Adolescent Health Services Care